2023
DOI: 10.48084/etasr.5251
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Graphical User Interface for Reflection Loss Calculation in Perovskite-RGO based Microwave Absorbing Composites

Abstract: In this paper, a novel method is investigated wherein the theoretical and mathematical analysis of the perovskite-Reduced Graphene Oxide (RGO) based composite microwave absorber is used to form a machine learning model using linear regression to predict the reflection loss and the effective dielectric permittivity of a selected perovskite compound in an RGO-based composite. At first, the theoretical derivation is carried out to find a mathematical relationship between the reflection loss and the dielectric per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Similarly, a prediction model was reported that correlates cationic radii and RL in perovskite‐RGO‐based MAMs. [ 163 ]…”
Section: Challenges Ahead: Identifying and Addressing Problemsmentioning
confidence: 99%
“…Similarly, a prediction model was reported that correlates cationic radii and RL in perovskite‐RGO‐based MAMs. [ 163 ]…”
Section: Challenges Ahead: Identifying and Addressing Problemsmentioning
confidence: 99%
“…( 18) reduces to s11(k) or RL(xk-1 -) and the input impedance Zin(k, xk -) reduces to that for WMB or MB. However, the input impedance of WMB or MB are usually applied wrongly to the intermediate layer [43,[56][57][58][59][60][61][62].…”
Section: The Relationship Of Reflection Coefficients Between Layersmentioning
confidence: 99%
“…Similar to the hierarchical structures with different interface organizations, multilayer film has been investigated for better microwave absorption [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Even though each layer k in the film shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, multilayer films, as depicted in Fig. 1, have been explored extensively to enhance microwave absorption performance [56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Although each layer (k) within the film possesses its unique r,k and r,k properties, these are effectively averaged out when all the layers in the film are considered as a whole.…”
Section: Introductionmentioning
confidence: 99%